SME development programs: a critical review / Charles Harvie and Boon-Chye Lee (Faculty of Business and Management ; UiTM Press, 2005)
This paper reviews and examines the arguments for government intervention in markets with the purpose of providing assistance to SMEs in a range of activities. This review suggests that many of the arguments put forward for subsidising SME activities (as distinct from some activities of firms regardless of size) are not economically justified. Nonetheless, it is widely acknowledged that SMEs suffer from disadvantage relative to large firms, principally in the areas of access to finance, information and technology. Innovative measures aimed at alleviating such disadvantages require particular attention by government.